Land Reforms, Status and Population Growth - Ulla Lehmijoki; Tapio K. Palokangas (Institute for the Study of Labor (IZA), 2014)
In this document, we consider the effects of a land reform on economic and demographic growth by a family-optimization model with sharecropping, endogenous fertility and status seeking. We show that tenant farming is the major obstacle to escaping the Malthusian trap with high fertility and low productivity. A land reform provides peasant families higher returns for their investments in land, encouraging them to increase their productivity of land rather than their family size. This decreases fertility and increases productivity in agriculture in the short and long runs. The European demographic history provides supporting evidence for this.
Keywords: O41; J13; N33; 330; land reforms; population growth; status seeking; sharecropping